A persistent plaque on the back of the hand. (1st April 2022) - Cameron, S.; Ramakrishnan, R.; Patel, N. P.
Abstract: We report the case of a 75‐year‐old woman presenting with acrodermatitis chronica atrophicans affecting the right hand dorsum, developing after an insect bite sustained in Greece. Diagnosis was confirmed by serology, PCR and histopathological findings. The plaque resolved following a 3‐week course of oral doxycycline. Click https://www.wileyhealthlearning.com/#/online-courses/4ebea04b-e4de-49d3-9bbb-0d3355007e92 for the corresponding questions to this CME article.